2012
DOI: 10.1136/tobaccocontrol-2012-050427
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned cigarette purchases and tobacco point of sale advertising: a potential barrier to smoking cessation

Abstract: Young adults and individuals making multiple quit attempts or planning to quit in the next month are more likely to make unplanned cigarette purchases. Reducing unplanned purchases prompted by tobacco POS advertising could improve the likelihood of successful cessation among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 13 publications
5
34
2
1
Order By: Relevance
“…Young adults aged 18 to 24 years are twice as likely as older adults to make unplanned cigarette purchases in response to point-of-sale advertising (36,37). There is a higher density of point-of-sale advertising in stores where youth frequently shop, including those close to schools and in low socioeconomic areas (38,39).…”
Section: Impact Of Tobacco Industry Practicesmentioning
confidence: 97%
“…Young adults aged 18 to 24 years are twice as likely as older adults to make unplanned cigarette purchases in response to point-of-sale advertising (36,37). There is a higher density of point-of-sale advertising in stores where youth frequently shop, including those close to schools and in low socioeconomic areas (38,39).…”
Section: Impact Of Tobacco Industry Practicesmentioning
confidence: 97%
“…14,15 A meta-analysis revealed that the odds that any given advertisement was smokingrelated was 70% higher in Black areas versus White areas. 11 In addition, point of sale advertising is associated with unplanned purchases of cigarettes, 16,17 higher craving, and lower rates of smoking cessation. 18,19 A related risk factor for smoking relapse is smoking cue reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Advertisement sale of cigarette cause smoking cessation more difficult and increased the risk to start smoking. Reduction of exposure to sale of cigarettes advertisement and cigarette display seen by consumers can reduce unplanned cigarette purchase and enhance the succession of smoking cessation [6,9]. Limitations of this study is the inclusion of using cross-sectional study so it is difficult to distinguish the variables that cause and the variables of effect.…”
Section: Discussionmentioning
confidence: 92%